Critical digital citizenship amid the political challenges posed by the COVID-19 pandemic - Carvalho, Joao Mauro Gomes Vieira de [UNESP]; Gomes, Luiz Roberto; Zuin, Antonio Alvaro Soares; Lastoria, Luiz Antonio Calmon Nabuco [UNESP] (Univ Federal Santa Maria, 2025)
The aim of this article is to promote a theoretical reflection on the concept of citizenship, taking as context the digital culture and social isolation during the COVID-19 pandemic. This is a theoretical-conceptual study that, based on some concepts present in the current literature on the subject, used classic texts of political philosophy to dimension the meaning of the concept of digital citizenship and its use in educational policies from a broader theoretical-philosophical perspective. In this sense, it is assumed that the ubiquity of digital communication technologies presents problems that require critical reflection from the entire society, in a broader historical perspective. In a world increasingly organized economically around digital algorithms, access to information for all citizens has become a central problem in democratic societies. However, the study demonstrates that guaranteeing access to information technologies is not enough for a democratic education in this context. The result of the theoretical reflection presented here demonstrates that it is also necessary to promote critical self- reflection on the processes of content manipulation and induction of thoughtless consumption of information. This requires incisive educational action, as a way of clarifying and discerning the elements that make up the universe of information, which reaches us through various channels. The conclusion advocates that the democratic participation of citizens will only be effective politically if they are guaranteed a full cultural education, with a real possibility of cultural inclusion and ethical-political engagement in issues involving social life in digital culture.
Keywords: Political education; Digital culture; Critical theory